2017
DOI: 10.4168/aair.2017.9.6.526
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Immunoglobulin Replacement on Asthma Exacerbation in Adult Asthmatics with IgG Subclass Deficiency

Abstract: PurposeRecurrent respiratory tract infection is a common manifestation of primary immunodeficiency disease, and respiratory viruses or bacteria are important triggers of asthma exacerbations. Asthma often coexists with humoral immunodeficiency in adults, and some asthmatics with immunoglobulin (Ig) G subclass deficiency (IgGSCD) suffer from recurrent exacerbations. Although some studies suggest a benefit from Ig replacement, others have failed to support its use. This study aimed to assess the effect of Ig rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 32 publications
0
16
0
2
Order By: Relevance
“…A potential contributing role of antibody deficiency in asthma has also been suggested by a small case‐control study which found that asthma patients are more likely to have a diagnosis of CVID or selective IgA deficiency than non‐asthmatic individuals, potentially accounting for the increased risk of bacterial infections in some individuals with asthma . A preliminary proof‐of‐concept study found that IVIG significantly reduces the frequency of asthma exacerbations and improved asthma control in adults with IgG subclass deficiency …”
Section: Impaired Airway Mucosal Defencementioning
confidence: 93%
“…A potential contributing role of antibody deficiency in asthma has also been suggested by a small case‐control study which found that asthma patients are more likely to have a diagnosis of CVID or selective IgA deficiency than non‐asthmatic individuals, potentially accounting for the increased risk of bacterial infections in some individuals with asthma . A preliminary proof‐of‐concept study found that IVIG significantly reduces the frequency of asthma exacerbations and improved asthma control in adults with IgG subclass deficiency …”
Section: Impaired Airway Mucosal Defencementioning
confidence: 93%
“…Different studies confirmed the positive impact of Ig replacement therapy in improving asthma control status, ameliorating airway obstruction and reducing the frequency of exacerbations in asthmatic and COPD patients with previously undiagnosed PAD [83][84][85]. This means a reduction in courses of oral corticosteroids, cumulative annual dose of oral corticosteroids, rescue antibiotic use and hospitalisations for acute COPD exacerbations, and has implication both in terms of quality of life and healthcare costs.…”
Section: Asthma and Copdmentioning
confidence: 94%
“…The dose of IVIG administered was recommended as 400 to 600 mg/kg every 3 to 4 weeks (or the equivalent given in divided doses once or twice a week subcutaneously) [5,27,28]. The present study evaluated the current status of IVIG replacement in adult asthmatics in a single tertiary hospital setting and demonstrated that 31.85% of the PID group patients had maintained IVIG (probably due to the high cost).…”
Section: Discussionmentioning
confidence: 81%
“…However, there have been a few studies demonstrating the efficacy of IVIG replacement in asthmatic patients with IgGSCD in whom monthly IVIG replacement significantly improved quality of life, diminished the number of infections and decreased the need for antibiotics and hospitalization [22,23]. Our previous multicenter trial demonstrated that IVIG replacement (> 6 months) in adult asthmatics with IgG 3 SCD could significantly reduce the frequency of respiratory infections and asthma exacerbations as well as improve asthma control asthma status and quality of life [5]. Once asthma exacerbation occurs, inflammations and remodeling pathways are activated, which result in the deterioration of lung function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation